Synchronous or Asynchronous: Students’ Perceptions on Online Learning During the Pandemic - Yulitriana (The Study Program of English Education of Palangka Raya University, 2021)
The terms synchronous and asynchronous learnings are becoming trendy nowadays as the full online learning is conducted in all levels of education in order to prevent the Covid-19 pandemic outbreak. Accordingly, it is prominent to investigate students’ perceptions towards synchronous and asynchronous learning based on their experiences in online learning during this pandemic. Survey design was used in this research and the sample were 42 students of English Education Study Program at a public university in Palangka Raya. The data were collected from the responses of questionnaire given to the students. The result indicates that the synchronous and asynchronous activities in online learning gives new experience for the students, and they prefer the combination of both in their online learning instead of having only synchronous or asynchronous meetings most of the time. Synchronous meetings equip the students when dealing with new or complicated concepts and keep their interest in learning while the asynchronous ones give the students their personal pace in learning as they can adjust their time and speed.